INFLUENCE OF INTEGRATED EFFECT OF INORGANIC AND ORGANIC FERTILIZERS WITH FLY ASH ON HEAVY METALS ACCUMULATION OF SOIL AND PLANT UNDER RICE CROP - KIRAN PATEL; AND A. K. PATEL, R. N. SINGH (The Bioscan, 2018)
A field study was carried out during kharif season of 2014-15 at farmer field, Ajirma village, Surajpur district, (Chhattisgarh), to study the integrated effect of inorganic and organic fertilizers with different doses of fly ash on heavy metals accumulation of soil and plant under rice crop. The test crop was rice var. MTU-1010. The maximum available Cr, Co, Ni and Pb content was noted in treatment 75% GRD + 60 t fly ash ha-1 + 5 t FYM ha-1 (0.27, 0.50, 0.43, and 1.76 mg kg-1 ) while the minimum in control (0.17, 0.43, 0.33 and 1.20 mg kg-1 ). The maximum Cr, Co, Ni and Pb content in grain was found in 75% GRD + 60 t fly ash ha-1 + 5 t FYM ha-1 ( 15.67, 0.68, 0.37 and 4.33 mg kg-1) where it was minimum (12, 0.30, 0.20 and 1.33 mg kg-1) in control. The maximum Cr, Co, Ni and Pb content in straw ( 27.0,1.67, 0.28 and 11 mg kg-1 ) was found in 75% GRD + 60 t fly ash ha 1 + 5 t FYM ha-1 where it was minimum (18.20, 0.83, 0.13 and 6.00 mg kg-1) in control.